Perilaku Makan Lutung Jawa (Trachypithecus auratus) di Pusat Rehabilitasi Lutung Jawa (JLC) Coban Talun Kota Batu - Fairuz Qory Amalia; Hari Santoso; Hasan Zayadi (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2023)
Javan langur population has decreased, because the natural habitat of Javan langurs is decreasing from year to year, in addition to the rampant fishing of langur for trading. In order to suppress and reduce the habitat destruction of these wild animals, an effective and sustainable land rehabilitation effort is needed by recording the types of forage plants that Javan langurs like and the behavior of Javan langurs in foraging for their food. One of the efforts made to create a natural breeding place. The purpose of this research is to determine whether there is a specific Javan langur eating behavior pattern, in addition to knowing whether there is a change in Javanese langur eating behavior towards the type of food given. This observation uses the Continuous Recording method of recording. The results obtained will be processed in a qualitative descriptive form (narrative). From the results of this study, it was found that there was a specific feeding behavior for each type of feed given based on the size of the leaves, when consuming calliandra with smaller leaves the langurs did not need to pick the leaves first, it was different when langurs ate mountain amethyst and telasih which were larger in size so they tended to picking and tearing it first to get smaller leaf size, and there is a change in the diet of the type of feed given, namely langurs tend to fight more for calliandra plants because calliandra has fruit as well as flowers and also smaller leaf size making it easier for langurs to eat it . This is also shown by the higher number of chews on calliandra, which is 25 chews for 10 seconds.